1997
DOI: 10.1523/jneurosci.17-18-06839.1997
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic Inhibition of the T-Type and High Voltage-Activated Ca2+Currents in the Primary Sensory Neurons ofXenopusLarvae

Abstract: The primary sensory Rohon-Beard (R-B) neurons of Xenopus larvae are highly analogous to the C fibers of the mammalian pain pathway. We explored the actions of 5-HT by studying the modulation of Ca 2ϩ currents. In ϳ80% of the acutely isolated R-B neurons, 5-HT inhibited the high voltage-activated (HVA) currents by 16% (n ϭ 29) and the T-type currents by 24% (n ϭ 41). The modulation of the T-type and the HVA currents was mimicked by selective 5-HT 1A and 5-HT 1D agonists: 8-OH-DPAT and L-694,247. The effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 63 publications
2
41
1
Order By: Relevance
“…Neurons containing 5-HT are present in the raphe nucleus of stage 37/38 tadpoles (Van Mier et al, 1986) and 5-HT has been shown to block initiation of swimming by both skin stimulation and dimming (Sillar and Simmers, 1994;Jamieson, 1997). 5-HT inhibition of responsiveness to skin stimulation involves presynaptic inhibition of primary afferent neurons (Sillar and Simmers, 1994) and an increase in their firing threshold (Sun and Dale, 1997). This presynaptic action of 5-HT contrasts with the postsynaptic action of GABAergic inhibition on spinal CPG neurons during the stopping response (Li et al, 2003) and, as we now propose, during attachment.…”
Section: Discussionmentioning
confidence: 50%
“…Neurons containing 5-HT are present in the raphe nucleus of stage 37/38 tadpoles (Van Mier et al, 1986) and 5-HT has been shown to block initiation of swimming by both skin stimulation and dimming (Sillar and Simmers, 1994;Jamieson, 1997). 5-HT inhibition of responsiveness to skin stimulation involves presynaptic inhibition of primary afferent neurons (Sillar and Simmers, 1994) and an increase in their firing threshold (Sun and Dale, 1997). This presynaptic action of 5-HT contrasts with the postsynaptic action of GABAergic inhibition on spinal CPG neurons during the stopping response (Li et al, 2003) and, as we now propose, during attachment.…”
Section: Discussionmentioning
confidence: 50%
“…The epidermis is separated from the underlying rudimentary dermis by a basement membrane. DRG neurons are not functional until ∼4 wk when the epidermis stratifies, and initially axons of unmyelinated Rohonbeard (RB) neurons with analogy to mammalian C-fibers (20) innervate the skin and arborize between both layers. To assess RB axon degeneration in transgenic Tg(isl2b:GFP) (21) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…7). Because amiloride blocks low-voltage-activated T-type calcium channels (Fox et al 1987;Tang et al 1988), this suggests currents carried by T-type channels contribute to depolarization in stage 37/38 RB neurons; such a role has been reported in Xenopus RB neurons at stage 42 (Sun and Dale 1997). In DL neurons, amiloride also affected depolarization, greatly reducing the AP peak and the rate of depolarization (Table 4 and Fig.…”
mentioning
confidence: 77%